An Insight into Uganda’s New Sentencing Guidelines: A Replica of Individualization? - Kamuzze, Juliet (Federal Sentencing Reporter, 2014)
The Ugandan Taskforce on developing sentencing guidelines recently drafted sentencing guidelines for Uganda, which were issued as practice directions by the Chief Justice to assist judges and magistrates in the sentencing decision making process. Like in many other jurisdictions, the sentencing guidelines have been developed to address the perceived existence of inconsistencies in sentencing of similarly placed offenders. This article offers the first insight into Uganda's new sentencing guideline reform. Part I offers some brief commentary on the nature of discretionary sentencing in Uganda. This is followed by a concise chronology of the historical origins of the guidelines, including a brief commentary on the Ugandan Supreme Court decision in the Kigula case that abolished the mandatory death penalty. This decision created a new era of discretionary capital sentencing in Uganda, which later precipitated the need for the development of the guidelines. The third section provides an insight into the main features of the sentencing guidelines, including the composition and mandate of the Ugandan Taskforce that drafted the sentencing guidelines and a brief commentary on the scope and contents of the guidelines. This section addresses some important weaknesses confronting the Uganda guidelines. The article suggests that the Ugandan Taskforce crafted the guidelines on a loose definition of consistency which has given consistency as the main goal of the guidelines a meaningless function. The article concludes that consistency would be given a meaningful function if Uganda's guidelines are modeled on a limiting retributivism justification.